Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1093/ajcn/32.11.2237
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin requirement of the adult human

Abstract: Young adult male subjects maintained on a metabolic ward were fed diets providing controlled intakes of thiamin and either 2800 or 3600 kcal. The higher level of calories was attained by an increased intake of carbohydrates. Constant weights were maintained by the subjects by adjusting daily activity and exercise schedules. Thiamin requirements were evaluated in terms of erythrocyte transketolase activity and urinary excretion of the vitamin. The results of the study revealed that a relationship exists between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…20 Treatment with thiamine decreased the blood pyruvate concentration by increasing TCA cycle flux. This treatment improved the myopathy and beriberi heart disease in patient 1 and decreased the blood concentrations of lactate and pyruvate in both patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Treatment with thiamine decreased the blood pyruvate concentration by increasing TCA cycle flux. This treatment improved the myopathy and beriberi heart disease in patient 1 and decreased the blood concentrations of lactate and pyruvate in both patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent lower extremity edema developed in the siblings at 15 years of age, which is when thiamine requirements become the greatest (i.e., in the second and third decades of life), because the thiamine requirement for humans is 0.5 mg/1,000 kcal/day. 20 The recommended daily thiamine requirements for Japanese males between 15 and 22 years of age is 1.3 mg/day compared to 1.4 and 1.5 mg/day for males in the USA. 9 In the present study, the first pedigree analysis demonstrated thiamine deficiency in the siblings and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some old data support the above view: Sauberlich et al 8 found that thiamin requirements in male subjects were 30% higher when daily energy intake was 15.1 MJ. (3600 kcal), compared with 11.7 MJ.…”
Section: Factors Potentially Affecting Micronutrient Requirements In mentioning
confidence: 90%
“…It has been proposed that thiamin [30] and ribo flavin [6] requirements are higher in the phys ically active, but these viewpoints have also been questioned [31,32], It is possible that the lack of changes in thiamin and riboflavin status indicators during the present exercise program was due to adequate dietary intakes or that the increase in total daily EE was not large enough.…”
Section: Discussionmentioning
confidence: 93%